The Impact of Social Media Usage Among Teenagers on the Indonesian Language in The Digital Era - Hasjim, Munira; Hasyim, Muhammad; ., Lukman; ., Kaharuddin; Rabiah, Sitti; Nadaring , Hasbullah (Journal of Ecohumanism, 2024)
Social media, with its advantages and disadvantages, has had a significant impact on the use of the Indonesian language, particularly among teenagers. Social media has shaped and transformed the way society communicates in Indonesian in daily life. The method used to analyze this issue is qualitative descriptive. Data collection techniques include screenshots to capture language usage phenomena on social media platforms such as WhatsApp, Instagram, TikTok, and Twitter (X), along with note-taking and documentation techniques. The research findings show that teenagers on social media employ linguistic aspects such as code-mixing, the use of informal language, phonetic reduplication and spelling variations, the use of acronyms and abbreviations, as well as emotional markers and symbols. The impact of social media on the Indonesian language includes vocabulary enrichment, degradation of language structure, maintenance of social and group identities, shifts in communication styles, and influences on the sustainability of standard language. Efforts to preserve the Indonesian language can be made through the government’s role in drafting policies and regulations that support language preservation in the digital era, educational institutions by adjusting the Indonesian language curriculum to the times, active societal campaigns promoting proper Indonesian usage on social media, and individual awareness and responsibility for using correct Indonesian in social media communication.